Living with a chronic physical health condition: the academic, social, and emotional experiences of adolescents - Hill, Julie Christine, author; Peila-Shuster, Jacqueline J., advisor; Anderson, Sharon K., committee member; Youngblade, Lise, committee member (Colorado State University. Libraries, 2014)
Interviews were conducted with 11 adolescents with chronic physical health conditions between the ages of 15 and 19. Participants also kept a journal of their daily experiences every day for one week. The purpose of the interviews and journals was to capture the academic, social, and emotional experiences of adolescents living with a chronic physical health condition. Findings from the current research study supported the findings from previous research studies conducted with adolescents with a chronic physical health condition. Both the current research study and previous research studies found that adolescents with chronic physical health conditions experience physical restrictions and obstacles, social and emotional restrictions and obstacles, and educational implications due to their chronic physical health condition. In addition to supporting previous findings, the current research study found that positive emotions and strengths helped adolescents with a chronic physical health condition cope with the challenges they experienced. Based on study results, implications for practice are provided for teachers, school counselors, career counselors, and other counselors when working with adolescents with chronic physical health conditions. Suggestions for further research are recommended, especially surrounding the use of the constructs of positive emotions, hope, and strengths to help adolescents with chronic physical health conditions cope with the challenges they experience.
Keywords: adolescents; chronic; conditions; health; illness; school